KONSEP MAKKIYAH DAN MADANIYYAH: ANALISIS MAKNA, CIRI, KLASIFIKASI, URGENSI, PANDANGAN ULAMA KLASIK DAN KONTEMPORER - Khoerunnisa, Ananda Salma; Anisa Fitriany Sholehah; Karman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research examines the concept of Makkiyah and Madaniyyah in the Qur'an, which was revealed gradually to Prophet Muhammad over a period of more than 23 years. The main focus is to analyze the meaning, characteristics, differences, classification, and views of classical and contemporary scholars regarding Makkiyah and Madaniyyah. This study also discusses the urgency and benefits of understanding this knowledge in Qur'anic studies. The classification of Qur'anic verses into Makkiyah and Madaniyyah categories is the result of ijtihad by scholars from among the companions and followers of the Prophet, rather than directly from the Prophet himself. This has led to variations in interpretation in understanding the chronology of the revelation of Qur'anic verses and chapters. The methodology used is a literature study, utilizing various literary sources including reference books and relevant journal articles. The result is an engaging exploration of how understanding Makkiyah and Madaniyyah can open new doors in comprehending the context, meaning, and relevance of the Qur'an.